2013
DOI: 10.1093/dnares/dst029
|View full text |Cite
|
Sign up to set email alerts
|

The Control Region of Mitochondrial DNA Shows an Unusual CpG and Non-CpG Methylation Pattern

Abstract: DNA methylation is a common epigenetic modification of the mammalian genome. Conflicting data regarding the possible presence of methylated cytosines within mitochondrial DNA (mtDNA) have been reported. To clarify this point, we analysed the methylation status of mtDNA control region (D-loop) on human and murine DNA samples from blood and cultured cells by bisulphite sequencing and methylated/hydroxymethylated DNA immunoprecipitation assays. We found methylated and hydroxymethylated cytosines in the L-strand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
223
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(265 citation statements)
references
References 49 publications
18
223
1
1
Order By: Relevance
“…25 Up until recently, it was thought that epigenetic modifications could only occur in nuclear DNA and not in mtDNA. Despite the discovery of the mtDNMT1 enzyme by Shock et al 12 and studies demonstrating mtDNA methylation in humans, 21,22,26 mammals, 21,23 and cultured cells, 21,27 there are still controversial studies reporting complete absence of mtDNA methylation in human cells lines 19 or questioning the clinical usefulness of this biological phenomenon. 20 Nevertheless, the rationale of studying mtDNA methylation is underscored by its role in the etiology of a variety of human diseases 13,[15][16][17] and aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Up until recently, it was thought that epigenetic modifications could only occur in nuclear DNA and not in mtDNA. Despite the discovery of the mtDNMT1 enzyme by Shock et al 12 and studies demonstrating mtDNA methylation in humans, 21,22,26 mammals, 21,23 and cultured cells, 21,27 there are still controversial studies reporting complete absence of mtDNA methylation in human cells lines 19 or questioning the clinical usefulness of this biological phenomenon. 20 Nevertheless, the rationale of studying mtDNA methylation is underscored by its role in the etiology of a variety of human diseases 13,[15][16][17] and aging.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Indeed, the functional consequences of this epigenetic mark are still under investigation but emerging evidence suggests a role in transcription modification of the mitochondrial genome. 16,17 For example, Bellizzi et al 21 confirmed that mtDNA is methylated at the displacement loop (D-loop), a crucial promoter region from which mtDNA replication and transcription are initiated. Furthermore, some authors have suggested that aberrant DNA methylation in the mitochondrial RNR1 (MT-RNR1) sequence, encoding for the mitochondrial ribosomal 12S rRNA (12S rRNA), could affect normal function and integrity of the mitochondrial ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…40 Interestingly, a study of mitochondrial DNA methylation has also reported that ~50% of methylcytosine within the D-loop region, which contributes to the regulation of mitochondrial DNA replication and transcription, was within non-CpG dinucleotides. 41 Collectively, these studies provide evidence that non-CpG methylation at gene promoters is associated with reduced gene expression. As discussed above, several lines of evidence implicate non-CpG methylation in the regulation of mitochondrial function.…”
Section: The Function Of Non-cpg Methylationmentioning
confidence: 91%
“…We believe that mitochondria having prokaryotic in its origin must have m6dA modifications preserved in its DNA. The human mtDNA contains both CpG as well as non-CpG methylation patterns (Barres et al, 2009;Bellizzi et al, 2013;Liu et al, 2016). No further work or exploration has been done for mitochondrial m6dA analysis, which is completely an unexplored as well as an exciting field to embark on.…”
Section: Resultsmentioning
confidence: 99%